Late Cretaceous planktonic foraminifera from Kerguelen Plateau (ODP Leg 183): new data to improve the Southern Ocean biozonation - M.R. Petrizzo (Cretaceous Research, 2001)
An almost complete Upper Cretaceous sedimentary sequence recently recovered on the Kerguelen Plateau (southern Indian Ocean) during ODP Leg 183 was analysed for planktonic foraminifera in order to refine and integrate the zonal schemes previously proposed for the Southern Ocean area. Detailed biostratigraphic analysis carried out on holes 1135A, 1136A and 1138A (poleward of 50°S palaeolatitude during Late Cretaceous time) has allowed recognition of low and mid-high latitude bioevents, useful for correlation across latitudes, in addition to known Austral bioevents. The low latitude biozonation can be applied to Turonian sediments, because of the occurrence of Helvetoglobotruncana helvetica, which marks the boundary between Whiteinella archaeocretacea and Helvetoglobotruncana helvetica zones. The base of the Whiteinella archeocretacea Zone falls within the uppermost Cenomanian-Turonian black shale level in Hole 1138A. The stratigraphic interval from upper Turonian to uppermost Santonian can be resolved using bioevents recognized in the mid-high latitude sections. They are, in stratigraphic order: the last occurrence of Falsotruncana maslakovae in the Coniacian, the first occurrence of Heterohelix papula at the Coniacian/Santonian boundary, the extinction of the marginotruncanids in the late Santonian, and the first occurrence of Globigerinelloides impensus in the latest (?) Santonian. The remainder of the Late Cretaceous fits rather well in the Austral zonal scheme, except that Globigerinelloides impensus exhibits a stratigraphic range in agreement with its record at the mid-high latitude sections and extends further downwards than previously recorded at southern sites. Therefore, despite the poor recovery in certain intervals and the presence of several hiatuses of local and regional importance as revealed by correlation among holes, a more detailed zonal scheme has been obtained (mainly for the less resolved Turonian-Santonian interval). Remarks on some species often overlooked in literature are also provided.